The plight of internally displaced communities: case of Tokwe Mukosi - Marungwara, Washington (Midlands Sate University, 2015)
This research was predominantly influenced by the ever increasing cases of internal displacement in Zimbabwe resulting in the impoverishment of the already poverty stricken communities countrywide. This study was also triggered by the Tokwe Mukosi 2014 flood disaster which generated evacuations of close to 3500 families to transit camps in Chingwizi, Chisase and Masangula lands. A qualitative exploratory descriptive design was used to identify, unravel, analyse and describe factors affecting displaced persons in Chingwizi and enable the researcher to properly organize the data collection process. The study results exposed that internally displaced victims face a wide array of challenges during and after displacement. Victims are exposed to poverty, unfavorable living conditions, hunger, deteriorating livelihoods and physical, verbal and sexual abuse at the hands of fellow victims or responsible authorities of which women are mostly at the receiving end. With that in mind, the research recommends for coordinated approaches to dealing with displacement victims and need to effectively do gender analysis and mainstream gender in aid disbursements. Further study should be carried out to identify how developed countries are addressing the issue of internal displacement.